2016
DOI: 10.1002/ppul.23415
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study on the utility and safety of EBUS‐TBNA and EUS‐B‐FNA in children

Abstract: EBUS-TBNA and EUS-B-FNA are safe techniques with a good diagnostic yield in the evaluation of children with mediastinal lymphadenopathy. Pediatr Pulmonol. 2016;51:1031-1039. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 42 publications
1
70
0
Order By: Relevance
“…The addition of EUS‐B‐FNA only in cases where the mediastinal lymph nodes were not accessible to EBUS‐TBNA, significantly increased the sensitivity of the procedure, which reached 100% in one study . The combined use of EBUS‐EUS‐B has been found safe and effective as part of the diagnostic evaluation in children with mediastinal lymphadenopathy …”
Section: Resultsmentioning
confidence: 99%
“…The addition of EUS‐B‐FNA only in cases where the mediastinal lymph nodes were not accessible to EBUS‐TBNA, significantly increased the sensitivity of the procedure, which reached 100% in one study . The combined use of EBUS‐EUS‐B has been found safe and effective as part of the diagnostic evaluation in children with mediastinal lymphadenopathy …”
Section: Resultsmentioning
confidence: 99%
“…This indication is rarer in children, though mediastinal masses are sometimes seen. Dhooria et al reported results from a retrospective multicenter study on the use of this method in 67 children (3‐17 years old) for the diagnostic evaluation of mediastinal lymphadenopathy. Eighty percent of these patients were biopsied using only sedation and spontaneous breathing.…”
Section: Diagnostic Testing/endoscopymentioning
confidence: 99%
“…To make a diagnosis, a tissue sample is needed, and traditionally this would be obtained via either open surgery or video-assisted thoracoscopic surgery. These procedures are invasive with a prolonged recovery time and potentially serious side effects 1. In adult medicine, less invasive methods of obtaining a biopsy have become routine, and these techniques are beginning to be used in the paediatric population (see table 1).…”
Section: Shivanthan Shanthikumar (Respiratory Fellow) and Jo Harrisonmentioning
confidence: 99%
“…No significant adverse events were reported. Dhooria et al 1 reviewed 67 paediatric patients who had either an EBUS TBNA performed, or the same equipment was placed in the oesophagus to obtain a transoesophageal biopsy (EUS-B-FNA). There was no difference in diagnostic yield between EBUS TBNA and EUS-B-FNA with a calculated diagnostic sensitivity of 79.1% for EBUS TBNA or EUS-B-FNA.…”
Section: Shivanthan Shanthikumar (Respiratory Fellow) and Jo Harrisonmentioning
confidence: 99%